Respuesta :
Check the procedures in the picture attached.
1. Since we are using direct substitution, the only thing we need to do is replace [tex]x[/tex] by [tex]6[/tex] (the quantity [tex]x[/tex] is approaching to) in our quantity to get:
[tex] x^{2} -6=0^{2} -6=-6[/tex]
We can conclude that the correct answer is B) -6
2. Again, since we are using direct substitution, th only thing we need to do is replace [tex]x[/tex] by [tex]3[/tex] (the quantity x is approaching to) to get:
[tex] x^{2} +8x-2= 3^{2} +8(3)-2=9+24-2=31[/tex]
We can conclude that the correct answer is D) 31
3. Direct substitution again, so we are going to replace [tex]x[/tex] in our quantity by [tex] \frac{ \pi }{2} [/tex] to get:
[tex]2e^{ \frac{ \pi }{2} } cos \frac{ \pi }{2} [/tex]
And since cosine of [tex] \frac{ \pi }{2} [/tex] is 0, and any quantity multiplied by zero is zero:
[tex]2e^{ \frac{ \pi }{2} } (0)=0[/tex]
We can conclude that the correct answer is A) 0
4. Here we need to so some algebra first. Notice that if we use direct substitution, the denominator will be zero, and we cannot divide by zero. So lets massage our quantity first:
[tex] \frac{ x^{2} -4}{x-2} = \frac{ x^{2} - 2^{2} }{x-2} = \frac{(x-2)(x+2)}{x-2} =x+2[/tex]
Now, we can use direct substitution to get:
[tex]x+2=2+2=4[/tex]
We can conclude that the correct answer is B) 4
1. Since we are using direct substitution, the only thing we need to do is replace [tex]x[/tex] by [tex]6[/tex] (the quantity [tex]x[/tex] is approaching to) in our quantity to get:
[tex] x^{2} -6=0^{2} -6=-6[/tex]
We can conclude that the correct answer is B) -6
2. Again, since we are using direct substitution, th only thing we need to do is replace [tex]x[/tex] by [tex]3[/tex] (the quantity x is approaching to) to get:
[tex] x^{2} +8x-2= 3^{2} +8(3)-2=9+24-2=31[/tex]
We can conclude that the correct answer is D) 31
3. Direct substitution again, so we are going to replace [tex]x[/tex] in our quantity by [tex] \frac{ \pi }{2} [/tex] to get:
[tex]2e^{ \frac{ \pi }{2} } cos \frac{ \pi }{2} [/tex]
And since cosine of [tex] \frac{ \pi }{2} [/tex] is 0, and any quantity multiplied by zero is zero:
[tex]2e^{ \frac{ \pi }{2} } (0)=0[/tex]
We can conclude that the correct answer is A) 0
4. Here we need to so some algebra first. Notice that if we use direct substitution, the denominator will be zero, and we cannot divide by zero. So lets massage our quantity first:
[tex] \frac{ x^{2} -4}{x-2} = \frac{ x^{2} - 2^{2} }{x-2} = \frac{(x-2)(x+2)}{x-2} =x+2[/tex]
Now, we can use direct substitution to get:
[tex]x+2=2+2=4[/tex]
We can conclude that the correct answer is B) 4
![Ver imagen cerverusdante](https://us-static.z-dn.net/files/d95/9e5957159c1b45b6e509041151b3caed.png)